2015
DOI: 10.7310/arfe.51.179
|View full text |Cite
|
Sign up to set email alerts
|

Main Point of Management for Organic Farmers’ Market Development

Abstract: In recent years, the number of organic farmers' market has increased. However, many of these have problems ensuring customer credit, attracting customers, and establishing management systems, among other things. In order to solve these problems, first, it is important that the manager of the market sets guidelines for store openings in a market and ensure that farmers adhere to these

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Similarly, most locallyfocused processors sold mainly organic products. The same cannot be said for other sites that promote chisan-chishō such as chokubaijo, where, even though the products offered are local, there is usually little commitment to organic (Ojima et al, 2015). Therefore, the study shows that marché are emerging as more 'organic friendly' sites of local consumption, and that are more attractive for organic producers.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Similarly, most locallyfocused processors sold mainly organic products. The same cannot be said for other sites that promote chisan-chishō such as chokubaijo, where, even though the products offered are local, there is usually little commitment to organic (Ojima et al, 2015). Therefore, the study shows that marché are emerging as more 'organic friendly' sites of local consumption, and that are more attractive for organic producers.…”
Section: Discussionmentioning
confidence: 79%
“…As mentioned previously, organic products have never been a central focus of chisan chishō oriented initiatives (Kimura and Nishiyama, 2008). In most chokubaijo, for example, the focus is on selling conventional agricultural products, and it is difficult to promote sales of organic produce (Ojima et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One final aspect regarding organic farmers’ interaction with institutionalised forms of chisan chishō relates to the growing popularity of marché (farmers’ markets). While marché were initially promoted through government projects, much of their subsequent expansion has occurred through grassroots initiatives, often by local organic farmers’ groups and non‐profit organisations (Ojima et al., 2015; Zollet & Maharjan, 2020). Table 1 also shows that farmers’ markets are the most common marketing channel among the respondents, although the interviews revealed that farmers did not see them as a major income‐generating channel but rather as spaces for (re)connection and resocialisation.…”
Section: Resultsmentioning
confidence: 99%
“…Marché are inspired by farmers' markets in Europe and North America and are meant to be a temporary 4 and urban-based version of direct sale markets, where farmers can meet consumers directly. This kind of farmers' market existed before the launch of the government project (Ojima et al, 2015), but the project is responsible for kickstarting the spread of marchés around Japan and for the popularisation of the term itself.…”
Section: Alternative and Hybrid Food Network In Japanmentioning
confidence: 99%